2022
DOI: 10.52380/mojet.2022.10.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Examining the factors affecting teachers’ use of digital learning resources with UTAUT2

Abstract: Digital learning resources include various tools and applications that effectively plan and evaluate instructions, increase student learning, and make the teaching process more efficient. Although digital learning resources are compatible with Generation Z students’ learning paths and are used to make the teaching planning, implementation, and evaluation process more practical, teachers do not frequently use them. This study aimsto determine the predictive powers of variables within the framework o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 53 publications
4
12
0
Order By: Relevance
“…Notwithstanding, the constructs in this research were adopted and adapted from numerous kinds of literature. For instance, the PE construct was derived from [6] and [9]. Also, the EE construct was deduced from [2] and [6].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notwithstanding, the constructs in this research were adopted and adapted from numerous kinds of literature. For instance, the PE construct was derived from [6] and [9]. Also, the EE construct was deduced from [2] and [6].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the PE construct was derived from [6] and [9]. Also, the EE construct was deduced from [2] and [6]. The SI construct was derived from [11] and [10].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the international literature has demonstrated that the target group is mostly comprised of university students (Goto, et al, 2021;Apandi, & Raman, 2020;Liu, & Yan, 2020), teachers (Tseng, et. al., 2022;Avcı, 2022), pre-service teachers (Fung, Smith, & Gandolfi, 2022;Mutambara, & Chibisa, 2022;Goto, Batchelor, & Lautenbach, 2021;Ning, & Dong, 2021;Bower, DeWitt, & Lai, 2020;Raman, & Don, 2013), and managers (Dakduk, et al, 2018). In addition, the topics include MOOCs (Tseng, et.…”
Section: Introductionmentioning
confidence: 99%